Effect of Amorphous Mg50ni50 on Hydriding and Dehydriding Behavior of mg2ni Alloy - Ordonez, S; Serafini, D (2011)
Composite Mg2Ni (25 wt.%) amorphous Mg50Ni 50 was prepared by mechanical milling starting with nanocrystalline Mg2Ni and amorphous Mg50Ni50 powders, by using a SPEX 8000 D mill. The morphological and microstructural characterization of the powders was performed via scanning electron microscopy and X-ray diffraction. The hydriding characterization of the composite was performed via a solid gas reaction method in a Sievert s-type apparatus at 363 K under an initial hydrogen pressure of 2 MPa. The dehydriding behavior was studied by differential thermogravimetry. On the basis of the results, it is possible to conclude that amorphous Mg50Ni50 improved the hydriding and dehydriding kinetics of Mg2Ni alloy upon cycling. A tentative rationalization of experimental observations is proposed. © 2011 Elsevier Inc. All rights reserved.